Scouring effect of river bed from the flow over pipe using CFD / Abbod Ali Mohammed Saeed - Abbod Ali, Mohammed Saeed (2015)
Pipes that are mounted on the river bed is mostly exposed to continuously strong flow field. This continuous flow field removes sand particles deposited around the pipe and creates a hole, which is known as local scour, and this phenomenon is known as scouring. Sometime this scouring is so intense that it leads to pipe’s demage. The aim of this study was to study the effect of bluff body shapes and gap between circular body and wall of sand bed and the turbulence models sensitivity study and effect of scour depth. A numerical investigation of incompressible and transient flow around circular pipe has been carried out at different five gap phases. Flow equations such as Navier-Stokes and continuity equations have been solved using finite volume method. Unsteady horizontal velocity and Kinetic energy square root profiles are plotted using different turbulence models and their sensitivity is checked against published experimental results. Flow parameters such as horizontal velocity under pipe, pressure coefficient, wall shear stress, drag coefficient, lift coefficient, bed roughness are studied and presented graphically to investigate the flow behavior around an immovable pipe and scoured bed. Results reveal that among existing turbulence models, the standard k-